2001
DOI: 10.1016/s0893-133x(00)00228-1
|View full text |Cite
|
Sign up to set email alerts
|

The Neurobiology and Genetics of Suicide and Attempted Suicide: A Focus on the Serotonergic System

Abstract: Neuro-receptors Major depression and suicidal behavior are independently related to altered serotonergic function (Mann and Stanley 1986). See Table 1 for a summary (Malone and Mann 1993;Owens and Nemeroff 1994;Stoff and Mann 1997;Mann 1998). In major depression there are fewer platelet serotonin transporters (5-HTT), lower CSF 5-HIAA (Mendels et al. 1972;Sjöström and Roos 1972; Ashcroft et al. 1973a Ashcroft et al. , 1973bPost and Goodwin 1974; Bowers 1974; Goodwin and Post 1977;van Praag and de Haan 1979… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
210
0
12

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(228 citation statements)
references
References 135 publications
6
210
0
12
Order By: Relevance
“…1 There is also a large body of evidence suggesting that neurobiological factors increase the predisposition to suicide. 2 In spite of some overlap, this neurobiological predisposition seems to be, to a considerable extent, different from that mediating risk to major depression or other psychopathological processes commonly present in suicide completers. 3 A number of investigations have illustrated the importance of the prefrontal regions in depression and suicidal behavior.…”
Section: Introductionmentioning
confidence: 99%
“…1 There is also a large body of evidence suggesting that neurobiological factors increase the predisposition to suicide. 2 In spite of some overlap, this neurobiological predisposition seems to be, to a considerable extent, different from that mediating risk to major depression or other psychopathological processes commonly present in suicide completers. 3 A number of investigations have illustrated the importance of the prefrontal regions in depression and suicidal behavior.…”
Section: Introductionmentioning
confidence: 99%
“…36 Additionally, in a recent study, Rosel et al 37 observed altered levels of 5-HT2A and 5-HT4 receptors and their respective intracellular signaling systems IP 3 and cAMP in hippocampi of suicides when compared to controls. A number of recent investigations have highlighted the potential for identification of genetic predisposing factors for depression 38 and suicidal behavior, 39 including WFS1 [40][41][42] and p75NTR, 43 among others. However, these studies have focused on expression levels of one or several genes at a time and compared suicides with or without psychopathology to controls, not providing an idea of the overall changes taking place in relation to suicide versus the ones related to major depression.…”
Section: Introductionmentioning
confidence: 99%
“…Findings common to some or all of these disorders include reduced cerebrospinal fluid concentrations of the 5-HT metabolite, 5-hydroxyindoleacetic acid, reduced hormonal responses to 5-HT drug challenge, and altered brain 5-HT receptor numbers (Mann et al, 1995;O'Keane et al, 1992;Coccaro et al, 1995;Dolan et al, 2001;Drevets et al, 1999;Stockmeier, 2003). In addition, selective serotonin reuptake inhibitors (SSRIs) have proved effective in their treatment, an action that is believed to be due to the enhancement of 5-HT neurotransmission (Bell and Nutt, 1998;Mann et al, 2001;Jetty et al, 2001;Nemeroff, 2002).…”
Section: Introductionmentioning
confidence: 99%